Altered Macrophage and Dendritic Cell Response in Mif−/− Mice Reveals a Role of Mif for Inflammatory-Th1 Response in Type 1 Diabetes - Yuriko Itzel Sánchez-Zamora; Imelda Juarez-Avelar; Alicia Vazquez-Mendoza; Marcia Hiriart; Miriam Rodriguez-Sosa (Journal of Diabetes Research)
Macrophage migration inhibitory factor (Mif) is highly expressed in type 1 diabetes mellitus (T1DM). However, there is limited information about how Mif influences the activation of macrophages (Mφ) and dendritic cells (DC) in T1DM. To address this issue, we induced T1DM by administering multiple low doses of streptozotocin (STZ) to Mif−/− or wild-type (Wt) BALB/c mice. We found that Mif−/− mice treated with STZ (Mif−/−STZ) developed lower levels of hyperglycemia, inflammatory cytokines, and specific pancreatic islet antigen- (PIAg-) IgG and displayed reduced cellular infiltration into the pancreatic islets compared to Wt mice treated with STZ (WtSTZ). Moreover, Mφ and DC from Mif−/−STZ displayed lower expression of MHC-II, costimulatory molecules CD80, CD86, and CD40, Toll-like receptor- (TLR-) 2, and TLR-4 than WtSTZ. These changes were associated with a reduced capacity of Mφ and DC from Mif−/−STZ to induce proliferation in ovalbumin-specific T cells. All the deficiencies observed in Mif−/−STZ were recovered by exogenous administration of recombinant Mif. These findings suggest that Mif plays a role in the molecular mechanisms of Mφ and DC activation and drives T cell responses involved in the pathology of T1DM. Therefore, Mif is a potential therapeutic target to reduce the pathology of T1DM.